2010
DOI: 10.1080/07315724.2010.10719814
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Supplementation Affects Body Weight, Lipids, and Lipid Peroxidation in Obese Subjects with Metabolic Syndrome

Abstract: Green tea beverage consumption (4 cups/d) or extract supplementation (2 capsules/d) for 8 weeks significantly decreased body weight and BMI. Green tea beverage further lowered lipid peroxidation versus age- and gender-matched controls, suggesting the role of green tea flavonoids in improving features of metabolic syndrome in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
237
2
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(262 citation statements)
references
References 44 publications
9
237
2
14
Order By: Relevance
“…In this context, green tea has been widely investigated. It is rich in polyphenols including epigallocatechin-3-gallate (EGCG) and epicatechin-3-gallate (ECG), which cause weight reduction in various animal models (Sae-tan et al, 2011;Wang et al, 2014) and obese subjects (Basu et al, 2010 shown some inconsistencies in this regard probably due to the heterogeneity of both protocols and populations used (for review see (Wang et al, 2014;Hursel et al, 2009;Phung et al, 2010)). …”
Section: Introductionmentioning
confidence: 99%
“…In this context, green tea has been widely investigated. It is rich in polyphenols including epigallocatechin-3-gallate (EGCG) and epicatechin-3-gallate (ECG), which cause weight reduction in various animal models (Sae-tan et al, 2011;Wang et al, 2014) and obese subjects (Basu et al, 2010 shown some inconsistencies in this regard probably due to the heterogeneity of both protocols and populations used (for review see (Wang et al, 2014;Hursel et al, 2009;Phung et al, 2010)). …”
Section: Introductionmentioning
confidence: 99%
“…In human pancreatic islets stimulated with high glucose, EGCG lowers insulin secretion along with a decrease of intracellular glutamate [23]. EGCG has been shown to reduce the body weight of obese subjects [24] and of various animal models [25,26], as well as to improve glucose tolerance in diabetic db/db mice [27]. However, the poor bioavailability of EGCG may limit its use and human trials have shown some inconsistencies [26,28].…”
Section: Preventing Obesity By the Limitation Of Insulin Secretionmentioning
confidence: 99%
“…28 However, chronic moderate to high dose daily GTE and EGCG use in healthy human volunteers was not shown to cause severe adverse effects or impair liver function. [29][30][31][32] Prior pharmacokinetic studies have established peak blood concentrations and exposures of EGCG associated with its safety and tolerability in healthy subjects. [30][31][32][33][34] In a study by Chow et al, following a single 800mg dose of EGCG in five healthy volunteers, AUC (min·µg/ml) ±SD was 167.1 ± 57.0, C max (ng/mL) was 438.5 ± 28.4 and t 1/2 (min) was 114.0 ± 33.3.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Prior pharmacokinetic studies have established peak blood concentrations and exposures of EGCG associated with its safety and tolerability in healthy subjects. [30][31][32][33][34] In a study by Chow et al, following a single 800mg dose of EGCG in five healthy volunteers, AUC (min·µg/ml) ±SD was 167.1 ± 57.0, C max (ng/mL) was 438.5 ± 28.4 and t 1/2 (min) was 114.0 ± 33.3. 35 In a multi-dose study by Chow et al, volunteers were randomly assigned to receive one of the five treatments for 4 weeks: 800 mg EGCG once/day, 400 mg EGCG twice/day, 800 mg EGCG as Polyphenon E once/day, 400 mg EGCG as Polyphenon E twice/day, or a placebo once/day (8 subjects/group).…”
Section: Discussionmentioning
confidence: 99%